2013
DOI: 10.3720/japt.78.68
|View full text |Cite
|
Sign up to set email alerts
|

Tight Oil Potential in Japan

Abstract: The Onnagawa Shale is bio-siliceous, Monterey-like and the main source rock in Japan, particularly in Akita basin, with fairly high potential. It is 500m thick in average and has TOC of 2% in average, up to 5% in part, and HI of 500 mg/gC typically. The Onnagawa is under review in the light of Shale oil/gas, comparing the Monterey shale. As the rst step, we have reviewed the Yuihara-Ayukawa eld, where the largest commercial oil & gas production from the Onnagawa Shale is ongoing. In the eld, various reservoirs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This tight reservoir is interpreted as part of the tight oil system of a continuous accumulation including the kitchen. The tight oil potential around this field is expected approximately 100 million bbl (Yokoi et al 2013). …”
Section: Introductionmentioning
confidence: 98%
“…This tight reservoir is interpreted as part of the tight oil system of a continuous accumulation including the kitchen. The tight oil potential around this field is expected approximately 100 million bbl (Yokoi et al 2013). …”
Section: Introductionmentioning
confidence: 98%
“…Shale samples used in the current study are from the Miocene Onnagawa formation (Acocella et al., 2008; Figure 1) collected from an outcrop of Akita Gojome area in northeastern Japan (39.9146767, 140.2466342). They are clay poor biosiliceous shales (Kamitsuji et al., 2013; Yokoi et al., 2012) with 68 vol% quartz, 27 vol% feldspar, 3 vol% kaolinite, 1 vol% chlorite, 0.5 vol% pyrite, and 0.5 vol% other minerals (see Figure S1 for XRD results). The He pycnometry showed that these samples have a very high connected porosity of about 34.5% similar to the results of Kamitsuji et al.…”
Section: Methodsmentioning
confidence: 99%
“…Another possibility that should be considered is the effect of igneous intrusions on thermal maturity. Yokoi et al (2013) demonstrated that in the Ayukawa oil & gas field, the Onnagawa Formation is mature even at depths shallower The stratigraphic columns were compiled using data from this study, the Japanese National Gas Association (1992) , and the Japanese Association for Petroleum Technology (1993) . Iwasa, 1962;Ujiie, 1995) .…”
Section: Petroleum Potential In Western Aomorimentioning
confidence: 99%
“…1) . A notable example of source rock for conventional and unconventional oil and gas exploration is the Onnagawa Formation in Akita Prefecture (Aoyagi and Omokawa, 1992;Japan National Gas Association, 1992; Japan Association for Petroleum Technology, 1993;Yokoi et al, 2013;Kumada et al, 2018) . Previous studies on the siliceous mudstones in the western Aomori Prefecture revealed that the Odoji Formation, cor relatable with the Onnagawa Formation, is a potential source rock for hydrocarbons (Aoyagi and Omokawa, 1992;Ujiie, 1995;Martizzi et al, 2020) .…”
Section: Introductionmentioning
confidence: 99%